Morbidity profile and health-seeking behavior of rural elderly near Vellore, India - Mark D. Flage; Dip Shukla; Chehan Herath; Ishan Sahu; Paige E. Williams; Charlotte Bolch; Vinod J. Abraham (Journal of Family Medicine and Primary Care)
The elderly population in India is growing, which presents a set of unique challenges for healthcare providers. Social changes in India are creating unique burdens for the Indian healthcare system that will shift elder care from family to other sources of care. In order to best serve the elderly of India, healthcare providers can be helped by information about patients with unmet needs. Health-seeking behavior (HSB) among Indian elderly can be a useful tool for healthcare providers seeking to allocate resources and serve their communities effectively. To better understand HSB for elderly in rural South India, we performed a cross-sectional study of HSB among elderly of age 60 and above in three rural villages near Vellore, India. We found a 93% prevalence of HSB for acute and chronic illnesses in our study population. Our data suggest that patients with certain chronic diseases may be less likely to seek treatment. We also found that the odds of being disease-free were 2.85 times more likely for males, compared to females. Finally, we saw no relationship between patients’ type of disease and their choice of government-run or private care facilities. Taken together, these data demonstrate a high level of community engagement by public health workers in the Vellore area. Our data can help inform local providers about potential gender differences in community health and disease types associated with low HSB. Context: Rural areas near Vellore, Tamil Nadu, India. Aims: To support public health efforts of local healthcare teams. Settings and Design: A cross-sectional study of HSB among rural elderly age 60+, located in three rural villages near Vellore, Tamil Nadu. Methods and Material: Participants included residents 60 years and older living in rural villages near Vellore. We asked through in-person interviews about demographics, chronic and acute morbidities, and HSB. Their answers were reviewed and analyzed with the statistical software package “R.” Results: Our participants near Vellore exhibited a high proportion of HSB, with 93% of affected individuals choosing to seek care. Despite the large number of different socioeconomic variables we studied, the only significant predictor of disease presence was gender, with males exhibiting much lower odds of reporting disease compared to females. We found no relationship between the type of illness and the type of healthcare facility approached for treatment. Finally, we found evidence of a relationship between the type of chronic illness suffered by a participant and whether the participant sought treatment at all. Conclusions: Public health efforts in the Vellore area have been highly successful compared to other parts of India and the world. Local providers may continue to improve patient engagement with healthcare by studying gender trends in morbidities and focusing on patients with less-common diseases.